Analysis of vitamin D levels in patients with and without statin-associated myalgia — A systematic review and meta-analysis of 7 studies with 2420 patients. (15th January 2015) - Michalska-Kasiczak, Marta; Sahebkar, Amirhossein; Mikhailidis, Dimitri P.; Rysz, Jacek; Muntner, Paul; Toth, Peter P.; Jones, Steven R.; Rizzo, Manfredi; Kees Hovingh, G.; Farnier, Michel; Moriarty, Patrick M.; Bittner, Vera A.; et al.
Abstract: Introduction: Vitamin D (vit D) deficiency may be associated with an increased risk of statin-related symptomatic myalgia in statin-treated patients. The aim of this meta-analysis was to substantiate the role of serum vitamin D levels in statin-associated myalgia. Methods: The search included PUBMED, Cochrane Library, Scopus, and EMBASE from January 1, 1987 to April 1, 2014 to identify studies that investigated the impact of vit D levels in statin-treated subjects with and without myalgia. Two independent reviewers extracted data on study characteristics, methods and outcomes. Quantitative data synthesis was performed using a fixed-effect model. Results: The electronic search yielded 437 articles; of those 20 were scrutinized as full texts and 13 studies were considered unsuitable. The final analysis included 7 studies with 2420 statin-treated patients divided into subgroups of patients with (n = 666 [27.5%]) or without (n = 1754) myalgia. Plasma vit D concentrations in the symptomatic and asymptomatic subgroups were 28.4 ± 13.80 ng/mL and 34.86 ± 11.63 ng/mL, respectively. The combination of data from individual observational studies showed that vit D plasma concentrations were significantly lower in patients with statin-associated myalgia compared with patients not manifesting this side effect (weighted mean difference − 9.41 ng/mL; 95% confidence interval: − 10.17 to − 8.64; p  < 0.00001). Conclusions: This meta-analysis provides evidence that low vit D levels are associated with myalgia in patients on statin therapy. Randomized controlled trials are necessary to establish whether vitamin D supplementation reduces the risk for statin-associated myalgia.